The needs and problems in epilepsy caregiving: A gualitive exploration - Lua, Pei Lin; Nor Khaira Wahida, Khairuzzaman; Zariah, Abdul Aziz; Foo, Jimmy Lee Kok (2015)
Objective: Living with epilepsy imposes great challenges on both patients and their family caregivers but most researchers only explored the impact on patients, with less attention given to family caregivers. Our study intended to explore the needs and problems of epilepsy family caregivers of epilepsy patients encountered during the caregiving process. Methods: Respondents were recruited from the Neurology Clinic of Hospital Sultanah Nur Zahirah (HSNZ), Kuala Terengganu. A semi-structured interview was conducted using openended and broad questions asking about their general experience in caregiving, daily routine activities, caregiving effects, caregiving difficulties and caregivers’ needs. The interviewed data were later transcribed into verbatim before further analysis using the QSR International’s NVivo10 software. Results: Fifteen Malay Muslim family caregivers between the age of 19 and 66 years participated. Most were females (53%), married (67%), with education level at secondary school or equivalent (73%) and were homemakers (40%). In particular, respondents expressed the need for extra support from their family members and experts in terms of physical (care relief), mental, and financial aspects. In addition, the major caregiving problems identified included: (i) emotional disturbances (sad, angry, depressed, and anxious); (ii) care giving challenges (family adjustments, physical burden, psychological burden, and time management); and (iii) financial issues (not working and limited family income). Some advantages in caregiving were also reported. Conclusion: In conclusion, their experiences while taking care of their loved ones in terms of feelings, beliefs and needs exposed the difficulties in caregiving, causing substantial emotional pressure which could later lead to poor quality of caregiving. ASEAN Journal of Psychiatry, Vol. 16 (1): Januray – June 2015: XX XX.